PENGARUH PENGETAHUAN, GAYA HIDUP, DAN FAKTOR SOSIAL TERHADAP KEPUTUSAN NASABAH DALAM MENGGUNAKAN KARTU KREDIT BANK BCA DI KOTA SEMARANG - Harminingtyas, Rudika; Budiono Saputra, Reza (Jurnal Ilmiah Fokus Ekonomi, Manajemen, Bisnis & Akuntansi (EMBA), 2024)
The aim of this research is to analyze the influence of Knowledge, Lifestyle and Social Factors on Customer Decisions in using BCA Bank Credit Cards. The population in this research is all BCA credit card customers in Semarang City whose population is unknown or unlimited (infinite population). The samples taken were 97 customers. The sampling technique used is Convenience Sampling. The data analysis tool used in this research is multiple linear regression analysis. Based on the research results: Partially there is a positive and significant influence between Knowledge on Customer Decisions obtained by t-count 2.123 > t table 1.661 or sig t 0.036 < 0.05. Partially there is a positive and significant influence between Lifestyle on Customer Decisions obtained t-count 2.607 > t table 1.661 or sig t 0.011 < 0.05, Partially there is a positive and significant influence between Social Factors on Customer Decisions obtained t-count 2.769 > t table 1.661 or sig t 0.007 < 0.05, H3 accepted. Simultaneously there is a positive and significant influence between Knowledge, Lifestyle and Social Factors on Customer Decisions, obtained by F-count 36.502 > F-table 2.703 or sig F 0.000 < 0.05. Keywords: Knowledge, Lifestyle, Social Factors, Customer Decisions